Respon Pertumbunan Tanaman Kedelai terhadap Bradyrhizobium japonicum Toleran Masam dan Pemberian Pupuk di Tanah Masam - Triadiati, ,; Mubarik, Nisa Rachmania; Ramasita, Yoan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The use of acid tolerant rhizobacteria such as Bradyrhizobium japonicum is one effort for increasing soybeanproductivity in acid soil. B. japonicum is a N-fixing bacteria that can promote soybean growth through symbiosis with thehost plants. The objective of this study was to investigate the growth and production of soybean var. Wilis inoculated by B.japonicum and NPK inorganic fertilizer application in acid soil. Two isolates of B. japonicum that were BJ 11(19) and BJ11(wt) were used as inoculant for soybean. BJ 11(19) was resulted by transposons mutagenesis, whereas BJ 11(wt) is a wild type of bacteria. Both isolates of B. japonicum were acid tolerant. Soybean was inoculated with BJ 11(19) and BJ 11(wt)combined with compost and nitrogen fertilizer (with two rates). The field experiment was conducted at Cikabayan, Darmaga,in a randomized complete block design with 12 treatments and 3 replicates. The results showed that application of the acidtolerant B. japonicum BJ 11(wt), compost, and nitrogen fertilizer (10 g m-2) increased the plant height, dry weight of shootsand roots, nodule number, dry weight of nodules, nitrogenase activity, number of pod and seed, seed weight, and nitrogencontent of seeds in acid soil.Keywords: acid soil, acid tolerant rhizobia, Bradyrhizobium japonicum, compost, nitrogen fertilizer